DINAMIKA KOMUNIKASI ORANG TUA DAN ANAK YANG KECANDUAN GADGET - Helin, Ranti; Melita, Yerah (Istek Widuri Jakarta, 2022)
This study examines the communication dynamics of parents with gadget-addicted children. The research method used is a qualitative approach, with purposive sampling, namely by taking a sample with a purpose, namely parents and their children who are addicted to gadgets. Data collection techniques through observation and interviews. Check the validity of the data by triangulation of sources and techniques. The theory used is the Relational Dialectical theory. The results of the study state that the dynamics of communication between parents and children are related to totality, parents and children or vice versa are very dependent on each other, and they cannot be alone, because they are an inseparable unit. Contradiction, that communication that occurs between parents and children is often colored by contradictions, contradictions or conflicts, because each individual has their own interests. In communication, there needs to be a decision to be made, in this case, parents have a big role or share in making decisions.